The first integral method and traveling wave solutions to Davey–Stewartson equation - Jafari, Hossein; Sooraki, Atefe; Talebi, Yahya; Biswas, Anjan (Nonlinear Analysis: Modelling and Control, 2012)
In this paper, the first integral method will be applied to integrate the Davey–Stewartson’s equation. Using this method, a few exact solutions will be obtained using ideas from the theory of commutative algebra. Finally, soliton solution will also be obtained using the traveling wave hypothesis.